Business strategies of cultural industries in the context of economic growth: a qualitative analysis of the cultural sector development in Peru 2005-2015 - Paredes Izquierdo, Juan Carlos (2017)
The article examines the relationship between economy and culture, especially how they impact each other. From this perspective, it analyzes the behavior and the business strategies of five cultural industries’ sub-sectors in Peru (publishing, film, radio, television and phonographic industries) in a sustained economic growth setting.